KEPEMILIKAN MANAJERIAL, KESEMPATAN INVESTASI, RISIKO FINANSIAL, DAN NILAI PERUSAHAAN YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA (ISSI) - Iwan Wijaya Mulyatno (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2014)
This research is aims to examine the influences of managerial ownership, investment opportunity set, and financial risk on firm value on The Manufacturing sector Companies in Indonesia Sharia Stock Index (ISSI) in the period 2008-2010. The populations in this research are listed companies in Indonesia Sharia Stock Index (ISSI), which amounts to 220 and sample as many as 45 companies, for 3 years from 2008 s / d 2010. Therefore, the total observation in this research are 135 companies and have been analyzed by multiple linear regression analysis model. The data used are secondary data of the financial statements. Hypothesis testing used F test and t test.The result of the t test indicates, that the managerial ownership variable significantly showed a negative influences on the firm value, these proved that the hypothesis present to be acceptable. For the Investment opportunity set variable reveal slight impacts on the firm value. As of the Financial risk variable ominously occurred positive influences on the firm value in the manufacturing sector companies listed on the Indonesia Stock Index Sharia (ISSI) observed in the of period 2008-2010.